Does the performance of financial technology (fintech) firms matter: evidence from North American and European fintech firms - Umar Kayani; Suzan Dsouza; Zafar Husain; Farrukh Nawaz; Fakhrul Hasan (Cogent Economics & Finance)
This study aims to empirically investigate the factors that affect profitability so that fintech businesses can take precautionary actions against notified threats and attempt to boost such factors to improve performance. Our study aims to ascertain the factors that influence the business performance (by using financial ratios) of the fintech industry in North America and Europe. The relationship between the variables is tested through panel data analysis and additional analyses, such as examining the relationship during the global financial crisis (2007–2009), pre-COVID-19, and COVID-19 periods, to support our baseline results. Finally, the results of the 2SLS analysis used to address endogeneity and reverse casualty issues support our results for robustness. The results reveal that liquidity and working capital have a positive and significant impact on profitability; however, leverage has a negative impact during crisis periods. This shows that firms are flexible and ready to go for the leverage option as well for their survival. This negative relationship supports pecking order theory. Our empirical results have significant implications for international investors and managers. Additionally, this study provides insightful information to policymakers to improve countries’ policies regarding fintech industry development and avoid financial anomalies.